Supervised machine learning in predicting depression, anxiety and stress using web-based big data: preserving the humanistic intellect - Mohammad Aidid, Edre; Musa, Ramli (2021)
Introduction; The validated Depression, Anxiety and Stress Scale, 21 items (DASS-21) offers an insight on categorizing individuals into severity of each condition. The advancement in public health big data provides a platform for early detection and prompt treatment of individuals. However, there are lacking evidence on prediction accuracy of these data using artificial intelligence methods.